PENGARUH PENGERJAAN AKHIR TERHADAP STABILITAS DlMENSI KAYU - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1992)
This study  was designed   to determine the ability  of six  commercial exterior finishes  (2 clear coats  and 4 opaque  coats)  in  protecting wood from   dimensional changes.   Two wood species,  jabon (Anthocephalus cadamba Miq.) and mangium (Acacia mangium Willd.)  were used in this study.   Samples were  seasoned to air-dry condition  (moisture content of 15-17%)and  then  divided into groups on the basis of treatments and groin orientation (radial and tangential).  Application of each exterior finish  was undertaken according to procedures  suggested by the finish  manufacturer. The  effectiveness of treatments to dimensionally  stabilize wood was determined by measurements of wood swelling within 72-hours  immersion and calculation of a.:d-.swelling efficiency (ASE). Results of observations made to this stage showed that the effect  of finishing on wood dimensional stability varied according  to wood species, grain orientation and type of finish  coat. Finishing had a greater dimensional stabilizing effect  on Jabon than mangium.  Reduction of swelling due to finishing was greater in tangential compared to radial boards.  The use of clear coats significantly gave less protection on wood stability than that of opaque coats.  Anti-swelling efficiency of all treatments markedly decreased with increasing period of  immersion.